The Ottoman administration in the Wilayat of Aleppo through the newspapers Al-Shahba and Etidal (Journal of the College of Basic Education, 2022)
The purpose of this research is not to prepare a study on the administrative conditions of the state of Aleppo by referring to whatWritten on the subject by researchers and historians who dealt with the outlines of the Ottoman administration.Many books have been published dealing with the conditions of the Arab states in the Ottoman Empire, but no study has been conducted.One article, as far as we know, is about the administrative situation in the Wilayat of Aleppo through the contents of local newspapers.issued in the state in the second half of the nineteenth century, although objectively it was the mostEffective in presenting state conditions